Re-investigation of the sector collapse timing of Usu volcano, Japan, inferred from reworked ash deposits caused by debris avalanche - Nakagawa, Mitsuhiro; Matsumoto, Akiko; Yoshizawa, Mitsuki (Frontiers in Earth Science, 2022)
It is essential to establish the timing of past sector collapse events at a volcanic edifice to evaluate not only the evolution of the volcanic system but also potential volcanic hazards. This can be done by determining the age of the collapse-generated debris avalanche deposits. However, without evidence of an associated magmatic eruption, it is impossible to recognize juvenile materials in these deposits. Thus, it is usually difficult to determine the precise age of sector collapse. Usu is a post-caldera volcano of the Toya Caldera (Hokkaido, Japan) and has been constructed since ca. 19–18 ka on top of the caldera-forming Toya pyroclastic flow deposits (Tpfl deposit: 106 ka). A sector collapse occurred after the formation of a stratovolcano edifice and produced the Zenkoji debris avalanche (ZDA) deposit with reported ages ranging from >20 to 6 ka. We investigated the tephrostratigraphy preserved in the soil above the ZDA deposit and in the surrounding area and recognized fine ash fall deposits at two locations, above and east of the ZDA deposit. The glass shards within these deposits were correlated with several tephra layers with the majority being derived from Tpfl deposits. Thus, these ash deposits should be considered reworked tephra. A considerable number of hummocks in the ZDA deposit were also composed of deformed and fragmented Tpfl deposits, which suggests that the ZDA bulldozed and partially incorporated the Tpfl deposit on the flank of the volcano. Deformation and fragmentation of the non-welded soft silicic Tpfl deposit during the transport and emplacement of the ZDA produced an accompanying ash cloud, which deposited the observed glassy, fine, ash fall units. Radiocarbon dating of soil samples directly below and above the reworked ash deposits allowed dating the sector collapse to ca. 8 ka. This age is much younger than previously proposed results. Based on our findings, the transport and emplacement mechanism of the sector collapse should be revised. Our study shows that reworked ash layers caused by the flow of a debris avalanche can be used as an indicator of the timing of a sector collapse of the volcano.